Doping Terhadap Kardiovaskular - Laksono, Sidhi; Hosea, Grace Trifena (Universitas Hamzanwadi, 2022)
Nowadays sports, especially competitive sports have a big role in the economy, business, entertainment, and politics. The use of doping, which is a product in the form of drugs or blood that is used to improve athletes' performance, can have a negative impact on the health of athletes, including cardiovascular health, so the use of doping is prohibited. The objective of this article is to provide information to readers on the dangers of doping, especially on cardiovascular. This article was written based on a comprehensive search using Google Scholar and Pubmed. Various kinds of doping can be used according to the needs of athletes in certain sports. One of the most commonly used doping substances is anabolic-androgenic steroids (SAA) which can be used to increase muscle mass and strength but have many negative effects such as increasing blood pressure during exercise and rest, high-density lipoprotein (HDL), myocardial infarction, arrhythmia, left ventricular dysfunction, sudden cardiac death and was assessed as cardiotoxic. In addition to SAA, other substances are also considered harmful to the health of athletes and other users who are not athletes, although there are substances whose effects on the cardiovascular system are still unclear.